THE ARCHETYPAL IMAGE OF THE FOLK AVENGER IN HNAT KHOTKEVYCH’S STORY “DOVBUSH”: THE ARTISTIC PARADIGM OF THE STRUGGLE FOR FREEDOM AND THE AFFIRMATION OF NATIONAL IDENTITY - Kurinna, Nataliia; Zinko, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
This article explores literary interpretations of the figure of Oleksa Dovbush in Ukrainian prose and drama, with particular attention to Hnat Khotkevych’s novella. It demonstrates that Dovbush’s image functions as a multifaceted artistic symbol, combining traits of a folk avenger, a romantic hero, and a cultural myth. Special focus is placed on the analysis of genre and stylistic features, as well as the relationship between literary portrayals and folkloric sources. The study reveals that the contrast between the historical figure and the legendary image provides depth and polysemy to artistic representation, shaping the ideological and symbolic dimension of the texts and highlighting the problem of collective memory. Methodology. The research employs a complex of general and specialized methods: analysis and synthesis to generalize literary findings; structural-semantic analysis to examine artistic features of Dovbush’s image; contextual analysis to interpret its functioning in prose and drama; comparative method to juxtapose different authorial interpretations with folklore; and elements of hermeneutics to deepen understanding of the symbolic and mythological dimensions of Dovbush in Ukrainian culture. The scientific novelty of the article lies in its comprehensive analysis of literary interpretations of Oleksa Dovbush in Ukrainian prose and drama, considered in relation to folkloric sources. It systematically traces how Hnat Khotkevych transformed the folk myth into his own artistic models, endowing Dovbush with features of a romantic hero, tragic avenger, or cultural symbol. The study also identifies the functioning of the contrast between historical figure and legendary image, which ensures the polysemantic ideological-symbolic dimension of the texts and actualizes the problem of folk memory in Ukrainian literature. The practical significance of the article is its applicability in teaching Ukrainian literature, particularly in studying the opryshky movement and its artistic interpretations. The findings may be useful for preparing lectures and seminars that illustrate the transformation of Dovbush’s historical figure into a cultural myth. The conclusions can serve as a basis for further research on poetics of contrast, symbolism, and mythologization in literature, opening perspectives for future studies of the interaction between folklore and authorial artistic models.